Family-centred service in paediatric acquired brain injury rehabilitation: Bridging the gaps - Taylor Jenkin; Taylor Jenkin; Vicki A. Anderson; Vicki A. Anderson; Vicki A. Anderson; Kate D'Cruz; Adam Scheinberg; Adam Scheinberg; Adam Scheinberg; Sarah Knight; Sarah Knight; Sarah Knight (Frontiers Media S.A., 2022)
BackgroundChildren and adolescents who sustain an acquired brain injury (ABI) can experience acute and ongoing difficulties in a range of cognitive and functional domains, and their families often experience significant life changes and challenges. Family-centred service is therefore considered best practice in paediatric ABI rehabilitation. Despite widespread acceptance of family-centred service in this context, recent literature indicates that family needs are often unrecognised and unmet following paediatric ABI. Although family-centred service was introduced in the field of developmental disability over five decades ago, there remains a lack of clarity about how this approach is implemented in practice. Additionally, limited literature has discussed the implementation of family-centred service in paediatric ABI rehabilitation despite key differences between ABI and developmental disability, including nature and timing of onset, rehabilitation foci, and impacts on families.AimsIn this review, we aim to: (i) outline common sequelae of paediatric ABI with a focus on family outcomes; (ii) summarise paediatric rehabilitation and highlight opportunities for family support and involvement; (iii) discuss and synthesise literature across paediatric ABI rehabilitation and family-centred service to highlight gaps in knowledge and practice; and (v) identify clinical implications and future research directions.ConclusionsThere is a clear need for greater clarity and consensus regarding the implementation of family-centred service in paediatric ABI rehabilitation. This review highlights the importance of providing professional development opportunities for clinicians to increase competency in practising in a family-centred manner, and opportunities to actively involve, empower and support families within rehabilitation. This review also emphasises the importance of services implementing relevant supports to address family needs where possible and developing clear referral pathways so that families can access further support elsewhere when needed.